Fears, discrimination and perceived workplace promotion. Issue 1 (17th October 2017) - Sheaffer, Zachary; Levy, Shalom; Navot, Edo
Abstract : Purpose: Past research about workplace promotion has focussed on factors that shape employees' perceptions for promotion. Yet, we still know little about how such undesirable factors as the fear of success (henceforth FoS) syndrome and perceived workplace discrimination affect perceived promotion and even less so how this relationship is mediated by self-efficacy and intrinsic motivation. The purpose of this paper is to propose a conceptual framework integrating these factors. Design/methodology/approach: A structural equation modelling procedure was employed to empirically test the model using data collected from employees in wide-ranging Israeli industries ( n =553). Findings: The path model indicates that initially, FoS and perceived discrimination negatively affect perceived chances of promotion. When however, self-efficacy and intrinsic motivation mediate this relationship, subjects perceive their promotion chances positively. Practical implications: Self-efficacy and intrinsic motivation may be employed to attenuate the potentially adverse effects of FoS and discrimination effects. Originality/value: FoS and perceived workplace discrimination are common phenomena, yet the authors show that they may be mitigated by heightened self-efficacy and amplified intrinsic motivation that help in sustaining perceived workplace promotion.